Proline-glucose Amadori compounds: Aqueous preparation, characterization and saltiness enhancement. (June 2021) - Wang, Yuran; Cui, Heping; Zhang, Qiang; Hayat, Khizar; Yu, Jingyang; Hussain, Shahzad; Usman Tahir, Muhammad; Zhang, Xiaoming; Ho, Chi-Tang
Graphical abstract: Highlights: Spray drying improved Amadori compound conversion from 3.6% to 69.2%. 20% salt reduction did not lower saltiness at Amadori compound dosages above 0.4%. Proline derived Amadori compound promoted aldosterone secretion in saliva. Abstract: Amadori rearrangement product (ARP) derived from proline and glucose was prepared in aqueous medium, and purified by ion exchange chromatography and identified by mass spectrometry and nuclear magnetic resonance spectrometry. The ARP was confirmed as 1-deoxy-1-L-proline-D-fructose (C11 H19 O7 N, 277 Da) with four main isomers. A preliminary vacuum dehydration coupled with subsequent spray drying was used to improve the yield of ARP conversion from 3.63% to 69.15%. Furthermore, the taste characteristics of spray dried ARP products were analyzed by electronic tongue and sensory evaluation. The results indicated that when the dosage of ARP products was above 0.4%, a 20% salt reduction could be achieved without reduction in the salty taste as well as having a significant enhancement in the umami attribute. The products at low- and medium- extents of reaction could stimulate more secretion of aldosterone in oral cavity and then improve its sensitivity to the salt, while the product at high- extent of reaction inhibits aldosterone secretion.